Seismic Behavior of Tunnel Form Building under Lateral Cyclic Loading - Nor Hayati Abdul Hamid; Shamilah Anuar; Haryati Awang; Mahmud Kori Effendi (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
A three-story single-unit tunnel form building (TFB) was designed using a non-seismic code of practice (BS 8110). Two one-third scale test models were constructed and tested under in-plane lateral cyclic loading and out-of-plane lateral cyclic loading, respectively. The specimens were tested at ±0.01%, ±0.1%, ±0.25%, ±0.5%, ±0.75%, ±1.0%, ±1.25%, ±1.5%, ±1.75% ±1.8, ±1.9% and ±2% drifts, after which severe cracks were observed on the wall-slab joints and wall panels. Subsequently, the damaged specimens were repaired and retrofitted by wrapping carbon fiber reinforced polymer (CFRP) around the damaged walls and affixing steel plates and steel angles at the wall-slab joints using several different repair and retrofitting schemes. The repaired specimens were retested using the same drifts. The comparison of the seismic behavior between unrepaired and repaired specimens was made based on visual observation of damage, hysteresis loops, lateral strength capacity, stiffness, ductility, and equivalent viscous damping. The experimental results showed that the repaired specimens were improved in terms of damage, lateral strength capacity, stiffness, ductility, and equivalent viscous damping. It is recommended to strengthen and rehabilitate tunnel form buildings after an earthquake using CFRP, additional shear walls, steel plates and steel angles.